(untitled) (Academicia Globe: Inderscience Research, 2024)
The prevalence of dental caries in Russia is very high and reaches 99%. Currently, the treatment of caries is reduced to excision of the affected tissues and prosthetics of the defect with filling materials. Pretreatment is the most time-consuming stage, the features of which depend on the location of the carious cavity (KP), the volume of the lesion and the group to which the teeth belong, the state of oral hygiene, the aesthetic requirements of the patient and the properties of the filling material